1987
DOI: 10.1007/bf00377918
|View full text |Cite
|
Sign up to set email alerts
|

Women in dental surgeries: reproductive hazards in occupational exposure to metallic mercury

Abstract: Eighty-one women (45 dentists and 36 dental assistants) occupationally exposed to metallic mercury underwent a toxicoclinical examination. Total mercury lebels (TMLs) were determined in scalp and pubic hair by cold vapour AAS. Furthermore a detailed questionnaire study was made concerning adverse reproductive events. TMLs in the hair of the exposed women examined exceeded significantly those determined in the hair of 34 controls not exposed to mercury. All exposed women had continued working during pregnancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(52 citation statements)
references
References 15 publications
0
49
1
2
Order By: Relevance
“…Under a steady state condition, the hair to blood Hg concentration ratio is about 250-300. However, when other groups such as dentists and gold miners are exposed to Hg 0 vapor (23,24) The high MeHg concentration in the hair samples from the exposed group was another interesting finding, even though the percentage of MeHg with respect to THg in this group was very low. People living in or nearby mining areas seldom eat fish of any kind, because these areas are mountainous, have no rivers with fish, and are distant from the sea.…”
Section: Discussionmentioning
confidence: 98%
“…Under a steady state condition, the hair to blood Hg concentration ratio is about 250-300. However, when other groups such as dentists and gold miners are exposed to Hg 0 vapor (23,24) The high MeHg concentration in the hair samples from the exposed group was another interesting finding, even though the percentage of MeHg with respect to THg in this group was very low. People living in or nearby mining areas seldom eat fish of any kind, because these areas are mountainous, have no rivers with fish, and are distant from the sea.…”
Section: Discussionmentioning
confidence: 98%
“…Occupational studies have identified similar effects in humans. Higher rates of birth defects have been detected in children of workers exposed to mercury, organic solvents, and other chemicals (6)(7)(8)(9). However, community studies, based on reported disease clusters around hazardous waste sites, have rarely been able to document significant increases in congenital defects in infants born to exposed individuals (10)(11)(12).…”
Section: Abnormalities; Hazardous Waste; Registriesmentioning
confidence: 99%
“…Mercury vapor has reproductive effects in occupationally exposed women (dental assistants and dentists), reports included abortion, stillbirth and menstrual disorders (irregularity, painful or hemorrhagic menstrual bleeding) [195]. Polymenorrhoea or oligomenorrhoea [196] and reduced fertility [197] it was also observed in women working in a lamp factory and dental assistants, respectively.…”
Section: Reprotoxicity Of Metalsmentioning
confidence: 99%